2011
DOI: 10.1038/labinvest.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 induces metastasis in esophageal squamous cell carcinoma by upregulating matrix metalloproteinase 13

Abstract: Esophagus squamous cell carcinoma (ESCC) is one of the most deadly malignances because of its high frequency of metastasis. Given the associations of MUC1 with ESCC and tumor metastasis, we explored a potential role of MUC1 in ESCC metastasis. Among 40 ESCC and 20 paired normal tissue specimens examined, we found a significant increase of MUC1 expression in ESCC and more importantly, that expression of MUC1 and MMP13 are strongly correlated in patients who had lymph node metastasis. Studies with cell models in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…Although many reports demonstrate that MMP13 is involved in the migration and invasion of various tumor and non-tumor cell types, including esophageal squamous cell carcinoma, cutaneous squamous cell carcinoma, and endothelial cells (Lopez-Rivera et al, 2005;Xu et al, 2012;Ye et al, 2011), the role of MMP13 in migratory VSMCs has been unclear. Our finding that Ang II treatment resulted in a significant increase of MMP13 expression in RAoSMCs is similar to a previous report in which Ang II induced production of MMP3 and MMP13 via the AT 1 receptor in osteoblasts (Nakai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many reports demonstrate that MMP13 is involved in the migration and invasion of various tumor and non-tumor cell types, including esophageal squamous cell carcinoma, cutaneous squamous cell carcinoma, and endothelial cells (Lopez-Rivera et al, 2005;Xu et al, 2012;Ye et al, 2011), the role of MMP13 in migratory VSMCs has been unclear. Our finding that Ang II treatment resulted in a significant increase of MMP13 expression in RAoSMCs is similar to a previous report in which Ang II induced production of MMP3 and MMP13 via the AT 1 receptor in osteoblasts (Nakai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(Meierjohann et al, 2010;Pan et al, 2011;Yu et al, 2011). The metastasis of esophageal squamous cell carcinoma induced by MUC1, one of the transmembrane mucins, was reported to be mediated by upregulation of MMP13 expression (Ye et al, 2011). Non-tumor endothelial cell migration is also mediated by MMP13 via nitric oxide activation (Lopez-Rivera et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, MUC1 is overexpressed in metastatic disease and becomes localized throughout the cell (16). In numerous types of tumors, MUC1 expression was reported to be correlated with aggressiveness, metastatic disease and poor prognosis (9)(10)(11)(12)(13)16,18). MUC1 expression was reported to accelerate tumor invasion and metastasis via the impairment of E-cadherin (10), decrease the binding of p120 catenin to E-cadherin (18), upregulate matrix metalloproteinase 13 expression (13) and activate Wnt/β-catenin abnormally (9).…”
Section: Discussionmentioning
confidence: 99%
“…ESD guidelines were previously based on hematoxylin and eosin staining; however, numerous studies have reported that the expression of cell adhesion molecules, cell surface molecules, membrane-associated mucin phenotypes and collagen phenotypes are associated with lymph node metastasis and prognosis of carcinomas in multiple organs (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Mucin 1, cell surface associated (MUC1) is a transmembrane member of the mucin family and has been reported to be associated with metastatic progression (16).…”
Section: Introductionmentioning
confidence: 99%
“…65 Up-regulation of MMP-13 is associated with the development of metastases in oesophageal squamous cell carcinoma. 69 MMP-9 may also regulate angiogenesis, perhaps by releasing VEGF from the extracellular matrix and making it more available to endothelial cells; 50 and yet overexpression of MMP-9 was found to be associated with improved survival in organ-confined prostate cancer; 70 clearly it is not a case of 'one biomarker fits all'. Interestingly, it has been suggested that the relatively better prognosis in Lynch syndrome-associated cancers may in part be explained by the finding that expression of MMP-1 and -9 is lower in these tumours than in their sporadic counterparts, resulting in less efficient matrix degradation of the peritumoural stroma which would facilitate tumour cell migration.…”
Section: Extracellular Matrixmentioning
confidence: 99%